Sensory Profile and Stability of a New Ready-to-Drink Passion Fruit Juice Beverage with Different Sweetener Systems - De Marchi, Renata (2012)
The aim of this work was to determine the sensory profile and stability of a new ready-to-drink passion fruit juice beverage sweetened with different sweetener systems: sucrose, aspartame, sucralose and an aspartame/acesulfame-K blend (4:1), during six months of storage. Samples of each beverage were stored at room temperature and under refrigeration, and were evaluated at 0, 60, 120 and 180 days of storage. Descriptive sensory profiles and the stability of the beverages were determined using a trained panel (n=8). The sweetener type played a very important role in the perception of color, sweet taste, sweet aftertaste and sour aftertaste. The beverages sweetened with sucrose and sucralose were the most stable with respect to those characteristics. In the beverages containing aspartame, on the other hand, the intensities of those descriptors were only preserved if stored under refrigeration. Storing the beverages under refrigeration was crucial to preserve the fresh fruit aroma and flavor characteristics in all the beverages, independently of the sweetener type, during at least 120 days of storage, period after which those characteristics started to decrease at the same time as the canned fruit aroma and flavor, overripe fruit aroma and fishy aroma and flavor increased. The results indicated that, based on the sensory profile, the best option of sweetener to be used in the ready-to-drink natural passion fruit juice beverage studied was the sucrose for the standard version and the sucralose for the light version.